A method for selectively depressing pyrite in low alkalinity copper-sulfur flotation separation

CN122999397APending Publication Date: 2026-10-30KUNMING METALLURGY INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611448643.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

综上,淀粉与石灰协同作用可显著抑制黄铁矿,但现有技术对其协同抑制机理研究较少,尤其未公开在黄铁矿表面选择性构筑由方解石型结晶碳酸钙与未改性可溶性淀粉构成的钙化-有机复合亲水膜的技术内容,亦未给出未改性可溶性淀粉与饱和石灰水在pH 9.0~10.0窗口内实现黄铁矿回收率降至10%量级而黄铜矿回收率保持83%以上的技术教导

Benefits of technology

与现有技术相比,本发明的有益效果体现在如下几个方面。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999397A_ABST
    Figure CN122999397A_ABST
Patent Text Reader

Abstract

The application discloses a method for selectively inhibiting pyrite in low-alkalinity copper-sulfur flotation separation, and belongs to the technical field of flotation separation of sulfide ores. The method comprises the following steps: adding saturated lime water into a slurry containing chalcopyrite and pyrite, adjusting the pH of the slurry to 9.0-10.0 and stirring, adding unchemically modified soluble starch and stirring, then adding a collector and stirring, and finally aerating and floating to make the chalcopyrite float with the froth product and the pyrite remain in the product in the tank. The application solves the problems of high lime consumption, decreased copper recovery rate and difficulty in comprehensive recovery of associated valuable elements in the traditional high-alkalinity process. In the flotation process, the soluble starch and calcium species selectively form a calcification-organic composite hydrophilic film containing calcite-type crystalline calcium carbonate on the surface of the pyrite, the pyrite recovery rate can be reduced to below 10%, and the chalcopyrite recovery rate can be kept above 83%. The application is mainly used for efficient flotation separation of copper-sulfur minerals under low-alkalinity conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sulfide ore flotation separation technology, specifically to a method for selectively inhibiting pyrite in low-alkalinity copper-sulfur flotation separation. Background Technology

[0002] Copper, as an important strategic metal resource, occupies a vital position in fields such as construction, electronics, and aerospace due to its excellent thermal conductivity, electrical conductivity, and ductility. Chalcopyrite is the most important industrial copper mineral. Chalcopyrite and its main associated mineral, pyrite, have similar surface properties and both exhibit good natural floatability. Achieving efficient and selective separation of copper and sulfur is a key technical challenge in the flotation of copper sulfide minerals.

[0003] Technical defects of high-alkali lime process. In order to achieve copper-sulfur flotation separation, the industry usually adopts high-alkali process represented by lime to suppress pyrite, that is, to add a lot of lime to the slurry and form a hydrophilic film on the surface of pyrite under high pH conditions, thereby hindering the adsorption of collector (Luo Fuhua, Liu Dan, Liu Yuebing, et al. Current status and research progress of copper-sulfur flotation separation [J]. Nonferrous Metals (Mineral Processing), 2026, 16(2): 322-338.). Extensive production practice has shown that this process has problems such as large lime consumption, high slurry viscosity, easy scaling and blockage of pipelines, and unstable production operation. The high-alkali environment will inhibit the flotation activity of chalcopyrite, resulting in a decrease in copper recovery rate. The inhibited pyrite is difficult to reactivate, which affects the recovery of sulfur resources. Associated valuable elements such as gold, silver, and molybdenum are also difficult to recover comprehensively due to the high-alkali conditions (Luo Fuhua, Liu Dan, Liu Yuebing, et al. Current status and research progress of copper-sulfur flotation separation [J]. Nonferrous Metals (Mineral Processing), 2026, 16(2): 322-338.; He Guichun, Wu Yipeng, Feng Jinni, et al. Research status of activators for pyrite inhibited by high alkali and high calcium [J]. Nonferrous Metals Science and Engineering, 2012, 3(2): 37-40.). He Guichun et al. conducted a special review on activators for high-alkali and high-calcium suppressed pyrite. The existence of such literature itself reflects that the reactivation of suppressed pyrite in high-alkali processes has long been a production burden (He Guichun, Wu Yipeng, Feng Jinni, et al. Research status of activators for high-alkali and high-calcium suppressed pyrite [J]. Nonferrous Metals Science and Engineering, 2012, 3(2): 37-40.).

[0004] Current Status of Research on Organic Depressants. Organic depressants have attracted attention in recent years for their wide availability, good selectivity, and environmental friendliness in the separation of copper and sulfides at low alkalinity. Feng et al. systematically reviewed the research progress on depressants for flotation separation of copper-iron sulfide minerals at low alkalinity, and listed the development of selective depressants under low alkalinity conditions as the main direction in this field (FENG Q, YANGW, CHANG M, et al. Advances in depressants for flotation separation of Cu-Fesulfide minerals at low alkalinity: A critical review[J]. International Journal of Minerals, Metallurgy and Materials, 2024, 31(1): 1-17.). Starch, as a natural polysaccharide, has shown potential in the flotation separation of sulfide minerals. The application and mechanism of starch-based modifiers in mineral flotation have been reviewed (Dai Sixing, Wang Qianqian, Liu Cheng, et al. Research progress on the application and mechanism of starch-based modifiers in mineral flotation [J]. Comprehensive Utilization of Minerals, 2021(4): 73-79.). The selective inhibition effect and mechanism of starch on sulfide minerals and gangue minerals have also been reviewed (Wei Min, Lü Jinfang, Zheng Yongxing, et al. Research progress on the selective inhibition effect and mechanism of starch on sulfide minerals and gangue minerals [J]. Mineral Conservation and Utilization, 2021, 41(2): 58-64.).

[0005] Applications and limitations of starch inhibitors. Regarding the inhibitory effect of starch-based agents on pyrite, Han et al. investigated the influence of starch on the surface properties of pyrite and chalcopyrite and its response to flotation separation at low alkalinity. They pointed out that the inhibitory effect of starch alone on pyrite is easily affected by fluctuations in process conditions such as pulp pH and concentration (HAN G, WEN S, WANG H, et al. Effect of starch on surface properties of pyrite and chalcopyrite and its response to flotation separation at low alkalinity[J]. MineralsEngineering, 2019, 143: 106015.). Fletcher et al. compared the effects of native starch, oxidized starch and carboxymethyl cellulose as copper-activated pyrite depressants (FLETCHER B, CHIMONYO W, PENG Y. A comparison of native starch, oxidized starch and CMC as copper-activated pyrite depressants[J]. Minerals Engineering, 2020, 156: 106532.), Valdivieso et al. disclosed a scheme using dextrin as a non-toxic depressant and xanthates as a collector to inhibit pyrite (VALDIVIESO AL, CERVANTEST C, SONG S, et al. Dextrin as a non-toxic depressant for pyrite in flotation with xanthates as collector[J]. Minerals Engineering, 2004, 17(9-10): 1001-1006.), and Ran et al. disclosed a scheme using soluble starch as a depressant to achieve the flotation separation of pyrite and arsenopyrite (RAN J, LI Y, ZHAO X, et al.). Utilization of soluble starch as the depressant toflotation separation of pyrite from arsenopyrite[J]. Separation andPurification Technology, 2023, 310: 123155.).Ran et al.'s study separated pyrite and arsenopyrite without using lime or recovering chalcopyrite. They only demonstrated the use of soluble starch to inhibit pyrite (RAN J, LI Y, ZHAO X, et al. Utilization of soluble starch as the depressant to flotation separation of pyrite from arsenopyrite[J]. Separation and Purification Technology, 2023, 310: 123155.).

[0006] A combination scheme of starch polysaccharides and inorganic reagents. Regarding the combined use of starch polysaccharides and inorganic reagents, Khoso et al. disclosed a pollution-free reagent system for the selective separation of chalcopyrite and pyrite. Using sodium tricarboxylate starch (TCSS) and calcium oxide as a combined reagent, copper-sulfur separation was achieved under low alkalinity conditions at pH 9. The recovery rate of pyrite in the copper concentrate was less than 19%, while the recovery rate of chalcopyrite was greater than 80% (KHOSO SA, LYU F, MENG X, et al. Selective separation of chalcopyrite and pyrite with a novel and non-hazardous depressant reagent scheme[J]. Chemical Engineering Science, 2019, 209:115204.). Khoso et al. also noted that TCSS requires a large dosage and also inhibits chalcopyrite to some extent, necessitating a reduction in the amount of TCSS used to mitigate this inhibition (KHOSO SA, LYU F, MENG X, et al. Selective separation of chalcopyrite and pyrite with a novel and non-hazardous depressant reagent scheme[J]. Chemical Engineering Science, 2019, 209:115204.). TCSS is a derivative obtained by chemically modifying starch through carboxylation, requiring a specialized modification and synthesis process, resulting in higher reagent costs and greater preparation complexity compared to unmodified starch.Khoso et al. reported the synergistic depression phenomenon of an organic and inorganic reagent on FeS2 surface (KHOSO SA, GAO Z, TIAN M, et al. The synergistic depression phenomenon of an organic and inorganic reagent on FeS2 in Cu-S flotationscheme[J]. Journal of Molecular Liquids, 2020, 299: 112-198.). Khoso et al. disclosed the selective inhibition of pyrite in a copper-iron flotation system using a functionalized modified biopolymer (KHOSO SA, HU Y, LIU R, et al. Selective depression of pyrite with a novel functionally modified biopolymer in a Cu-Fe flotation system[J]. Minerals Engineering, 2019, 135:55-63.). Khoso et al. disclosed the selective separation of chalcopyrite from pyrite using a pollution-free and degradable inhibitor (KHOSO SA, HU Y, LYU F, et al. Selective separation of chalcopyrite from...). pyrite with a novel non-hazardous biodegradable depressant[J]. Journal of Cleaner Production, 2019, 232: 888-897.), the organic components used in the above literature are also chemically modified starch derivatives or modified biopolymers.

[0007] Other implementation pathways for combined depressants. Regarding other implementation pathways for combined depressants, Ai et al. disclosed the use of a combined depressant composed of starch and pyrogallic acid in a 1:1 ratio for copper-sulfur separation in low alkaline media and investigated its inhibition mechanism (AI G, ZHOU Y, WANG Y. A study on the combined depressant for the Cu-Sseparation in low alkaline medium and its depressing mechanism[J]. ProcediaEngineering, 2015, 102: 338-345.). Li et al. combined experiments, HSC simulations, DFT calculations and ToF-SIMS to study the inhibition mechanism of combined depressants on pyrite in a low-alkaline system (LI S, YUAN J, DING Z, et al. The depression mechanism on pyrite in a low-alkaline system with combined depressants: Experiment, HSC, DFT and ToF-SIMS studies[J]. PhysicochemicalProblems of Mineral Processing, 2023, 59(3): 168454.). The combination inhibitors of Ai et al. and Li et al. both contain combinations of organic and inorganic or organic components, but none of them involve the combination of unmodified soluble starch and saturated lime water within the pH window of 9.0 to 10.0, nor do they involve the crystal structure of the calcified-organic composite hydrophilic film on the pyrite surface.

[0008] In Chinese patent literature, Kunming University of Science and Technology's patent ZL202510257272.8 discloses a flotation method for arsenic-containing copper sulfide ore. It uses lime and dextrin as a combined inhibitor of pyrite, achieving selective inhibition of pyrite at a low alkalinity of pH 8.5 to 9.5. The steps involve adding lime to a ball mill, and then sequentially adding dextrin, a composite collector, and a frother to the coarsely ground material. The process route is sulfur inhibition, copper-arsenic co-flotation, regrinding and de-removal, and copper-arsenic separation (Kunming University of Science and Technology. A flotation method for arsenic-containing copper sulfide ore: China, ZL202510257272.8[P]. 2025-04-18.). Dextrin is a hydrolytic degradation product of starch, belonging to the same starch-based polysaccharide category as soluble starch, but with different molecular weight distribution and hydroxyl accessibility. Furthermore, this patent focuses on separating arsenic-containing copper sulfide ore and does not address the surface product structure of calcite-type crystalline calcium carbonate composite films. Patent CN116532244A from China ENFI Engineering Technology Co., Ltd. and China Nonferrous Engineering Co., Ltd. discloses a low-alkalinity inhibitor and method for pyrite in copper-sulfur ores containing secondary copper (China ENFI Engineering Technology Co., Ltd., China Nonferrous Engineering Co., Ltd. Low-alkalinity inhibitor and method for pyrite in copper-sulfur ores containing secondary copper: China, CN116532244A[P]. 2023-08-04.), patent CN103691569B from Northwest Research Institute of Mining and Metallurgy discloses a flotation method for high-sulfur gold-copper ores, in which lime is added to an emulsion with a weight concentration of 10% to 15% (Northwest Research Institute of Mining and Metallurgy. A flotation method for high-sulfur gold-copper ores: China, CN103691569B[P]. 2015-09-30.), and patent CN114011581A from Kunming University of Science and Technology discloses a method for preparing an inhibitor for copper-sulfur separation under weakly acidic conditions and its application (Kunming University of Science and Technology). A method for preparing an inhibitor for copper-sulfur separation under weakly acidic conditions and its application: China, CN114011581A[P]. 2023-03-24.). None of the above patent documents disclose a formulation in which lime is added in the form of saturated lime water in a metered manner and then mixed with unmodified soluble starch in stages.

[0009] There is a long-standing unresolved technical need in this field. In summary, the synergistic effect of starch and lime can significantly inhibit pyrite, but there is limited research on the synergistic inhibition mechanism in existing technologies. In particular, the technology for selectively constructing a calcified-organic composite hydrophilic film composed of calcite-type crystalline calcium carbonate and unmodified soluble starch on the pyrite surface is not disclosed. Furthermore, no technical guidance has been provided on achieving a pyrite recovery rate of 10% and a chalcopyrite recovery rate of over 83% using unmodified soluble starch and saturated lime water within a pH window of 9.0–10.0.

[0010] This invention addresses the aforementioned long-standing technical challenges by employing a reagent formulation involving the sequential segmented preparation of saturated lime water and unmodified soluble starch, precise control of the pH window (9.0–10.0), and selective construction of a calcite-type crystalline calcium carbonate-starch composite hydrophilic film on the pyrite surface. This provides a copper-sulfur flotation separation method that simultaneously achieves efficient pyrite inhibition and full recovery of chalcopyrite under low alkalinity conditions. Summary of the Invention

[0011] To address the aforementioned problems in the existing technology, this invention provides a method for selectively inhibiting pyrite in low-alkalinity copper-sulfur flotation separation. Under the premise of eliminating the starch chemical modification and synthesis process, the method enhances the selective inhibition of pyrite within a low-alkalinity window of pH 9.0 to 10.0, while maintaining the good floatability of chalcopyrite. The inhibition effect is confirmed by the surface product structure and flotation kinetic parameters.

[0012] To achieve the above objectives, the technical solution adopted in this invention is a method for selectively inhibiting pyrite in low-alkalinity copper-sulfur flotation separation. Saturated lime water is first added to a slurry containing chalcopyrite and pyrite to adjust the slurry pH to 9.0–10.0 and stir. Then, unmodified soluble starch is added and stirred. Next, a collector is added and stirred, followed by aeration flotation. Chalcopyrite floats to the surface with the froth product, while pyrite remains in the product in the tank. During the flotation process, the soluble starch and calcium species provided by the saturated lime water selectively form a calcified-organic composite hydrophilic film on the surface of pyrite. The calcified-organic composite hydrophilic film contains calcite-type crystalline calcium carbonate and soluble starch adsorbed on the surface of pyrite.

[0013] Preferably, the pH of the pulp is 9.2–9.6. Preferably, the soluble starch is soluble starch prepared from corn starch, and its mass concentration in the pulp is 100–200 mg / L, more preferably 150 mg / L. Preferably, the collector is butyl xanthate, and its concentration in the pulp is 1 × 10⁻⁶ mg / L. -4 mol / L. Preferably, after adding saturated lime water, stir for 3 min; after adding soluble starch, stir for 3 min; after adding collector, stir for 2 min; and the aeration flotation time is 2 min. Preferably, the solids in the slurry are chalcopyrite and pyrite minerals with a particle size of -74 to +38 μm, and the minerals are ultrasonically cleaned for 30 min before flotation to remove the surface oxide film.

[0014] In this invention, the flotation separation effect is characterized by the recovery rate. After aeration flotation, foam products and products in the tank are collected separately, filtered, dried and weighed, and the recovery rate ε is calculated according to formula (1).

[0015] (Formula 1) In equation (1), w 精 For the quality of foam products, w 尾 The quality of the products in the tank.

[0016] In this invention, flotation selectivity is further characterized by flotation kinetic parameters. Foam products were collected at 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 4 min and 5 min after the start of aerated flotation, and the cumulative recovery rate was calculated according to formula (1). The cumulative recovery rate was fitted using the classical first-stage flotation kinetic model according to formula (2).

[0017] ε t =ε ∞ (1 -e) -kt ) (Formula 2) In equation (2), ε t Let ε be the cumulative recovery rate at time t. ∞ Let ε represent the maximum theoretical recovery, and k be the flotation rate constant. After fitting, the ε of pyrite... ∞ The value is 30%–35%, and k is 0.14–0.17 min. -1 ε of chalcopyrite ∞ Not less than 93%, k not less than 0.90min -1 Goodness of fit R 2 Greater than 0.99.

[0018] In this invention, the surface product structure of the calcified-organic composite hydrophilic membrane was confirmed by infrared spectroscopy and X-ray photoelectron spectroscopy. The infrared spectrum of the calcified-organic composite hydrophilic membrane is in the range of 1430–1440 cm⁻¹. -1 and 870–880 cm -1 The characteristic absorption peak of calcite-type calcium carbonate appears at 571 cm⁻¹. -1 The nearby Fe-S lattice vibration peaks disappear; after treatment by the method, the proportion of Fe(III)-O / OH component on the pyrite surface is not less than 18%, the flotation recovery rate of pyrite is not higher than 10%, and the flotation recovery rate of chalcopyrite is not less than 83%.

[0019] Beneficial effects Compared with the prior art, the beneficial effects of the present invention are reflected in the following aspects.

[0020] With higher inhibition strength and lower required alkalinity, existing technologies achieve pyrite recovery rates below 19% in copper concentrate at pH 9. The synergistic system of this invention further reduces pyrite recovery to the 10% level; it also offers superior selectivity while largely preserving chalcopyrite floatability. Under the synergistic system, chalcopyrite recovery remains above 83%, with minimal impact from starch concentration variations; within the experimental range, chalcopyrite recovery remains above 90%. This invention uses unmodified soluble starch, minimizing the impact of the reagent formulation on chalcopyrite flotation and eliminating the need for starch chemical modification and synthesis. Kinetically, it achieves excellent copper-sulfur separation. Attached Figure Description

[0021] Figure 1 The effects of soluble starch dosage and pulp pH on the flotation recovery rates of chalcopyrite and pyrite were investigated. Figure 2 The effects of lime and soluble starch on the Zeta potential of chalcopyrite and pyrite surfaces; Figure 3 FT-IR spectra of chalcopyrite and pyrite under different reagent regimes; Figure 4 XPS spectra of chalcopyrite surface under different reagent regimes; Figure 5 XPS spectra of pyrite surface under different reagent regimes; Figure 6 The flotation kinetics data of lime and soluble starch on chalcopyrite and pyrite are used as well as the fitting curves of the classical first-stage flotation kinetic model. Detailed Implementation

[0022] The technical solution of the present invention will be further described below with reference to the accompanying drawings, embodiments, and test examples. The raw materials, equipment, and testing methods used in the following embodiments and test examples are as follows. The embodiments and test examples are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.

[0023] Figure 1 The effects of soluble starch dosage and pulp pH on the flotation recovery rates of chalcopyrite and pyrite were investigated. Figure 1 (a) The effect of the amount of soluble starch added on the flotation recovery of the two minerals when only soluble starch is added. Figure 1 (b) The effect of pulp pH on the flotation recovery of the two minerals under saturated lime water conditioning conditions; Figure 2 The effects of lime and soluble starch on the zeta potential of chalcopyrite and pyrite surfaces, among which... Figure 2 (a) is chalcopyrite. Figure 2 (b) is pyrite; Figure 3The FT-IR spectra of chalcopyrite and pyrite under different reagent regimes are shown. Figure 3 (a) is chalcopyrite. Figure 3 (b) is pyrite; Figure 4 XPS spectra of chalcopyrite surface under different reagent regimes, among which Figure 4 (a) is the Fe 2p spectrum. Figure 4 (b) is the S 2p spectrum. Figure 4 (c) is the Cu 2p spectrum. Figure 4 (d) is the Ca 2p spectrum; Figure 5 XPS spectra of pyrite surface under different reagent regimes, among which Figure 5 (a) is the Fe 2p spectrum. Figure 5 (b) is the S 2p spectrum. Figure 5 (c) is the Ca 2p spectrum; Figure 6 The flotation kinetics data of lime and soluble starch on chalcopyrite and pyrite, and the fitting curves of the classical first-stage flotation kinetic model are shown. Figure 6 (a) is chalcopyrite. Figure 6 (b) is pyrite.

[0024] I. Experimental Materials and Equipment The pure chalcopyrite and pyrite minerals used in the experiment were both obtained from a mine in Yunnan Province. After hand sorting to remove impurities, crushing, and screening, high-purity minerals of different particle sizes were obtained. The chemical multi-element analysis results of chalcopyrite and pyrite are shown in Table 1. As shown in Table 1, the contents of Cu, Fe, and S in the chalcopyrite used in the experiment were 32.94%, 30.02%, and 33.47%, respectively, with a purity of 96.43%; the contents of Fe and S in the pyrite were 45.39% and 53.15%, respectively, with a purity of 98.54%.

[0025] Table 1. Results of multi-element chemical analysis of the raw ore (mass fraction, %) The lime and soluble starch (SS, corn starch) used in the experiment were all analytical grade reagents, and the butyl xanthate (SBX) was industrial grade butyl xanthate. The lime was added in the form of saturated lime water, that is, it was added to the slurry as a saturated Ca(OH)2 solution and also served as a pH adjuster for the slurry.

[0026] Micro-flotation and flotation kinetics experiments were conducted using an XFG hanging cell flotation machine with a flotation cell volume of 70 mL and an impeller speed of 1500 r / min. Mineral surface cleaning was performed using a KQ-700DE CNC ultrasonic cleaner (Kunshan Ultrasonic Instruments Co., Ltd.). Zeta potential measurements were performed using a Zetasizer-3000HS potential probe analyzer (Malvin Instruments Ltd., UK). Infrared spectroscopy measurements were performed using a Nicolet iS50 Fourier transform infrared spectrometer (Thermoelectric Nielsen Instruments, Inc., USA). XPS analysis was performed using a Thermo Scientific ESCALAB 250Xi X-ray photoelectron spectrometer (Thermo Fisher Scientific, Inc., USA). Spectral data were analyzed and peak fitted using Avantage software, with the binding energy of epiphytic carbon (C1s) set to 284.8 eV during calibration.

[0027] II. Implementation Examples

[0028] Example 1: Determination of the amount of soluble starch. 2.0 g of pure mineral with a particle size of -74±38 μm was added to 100 mL of deionized water and ultrasonically washed for 30 min to remove the oxide film on the mineral surface. After discarding the supernatant, the mixture was transferred to a flotation cell and stirred for 2 min. Saturated lime water, SS, and SBX were added sequentially, with SBX dosage being 1×10⁻⁶. -4 The concentration of SS was mol / L, and the stirring time after adding the reagent was 3 min, 3 min and 2 min respectively. The flotation time was 2 min. The froth product (concentrate) and the product in the tank (tailings) were collected respectively. The recovery rate was calculated according to the quality of the concentrate and tailings according to formula (1). Each test was repeated 3 times and the average value was taken. When only SS was added to treat the ore sample, the change of SS concentration had little effect on the recovery rate of chalcopyrite. The recovery rate of chalcopyrite remained above 90% within the test range. When the amount of SS was higher, it had a certain inhibitory effect on pyrite. When the amount of SS was 150 mg / L, the recovery rate of pyrite could be as low as 31.33%. If the amount of SS was further increased, the recovery rate of pyrite fluctuated at about 30%, indicating that the inhibitory effect of further increasing the amount of starch on pyrite tended to be stable. Therefore, the amount of SS was determined to be 150 mg / L in the subsequent study. The results are shown in Figure 1 (a).

[0029] Example 2: Low alkalinity window and synergistic inhibition effect. The pH of the pulp was adjusted using saturated lime water. The effect of pulp pH before and after SS treatment on the flotation recovery rates of chalcopyrite and pyrite was investigated. The experimental method was the same as in Example 1, and the results are shown in […]. Figure 1(b) Regardless of the addition of SS, the recovery rate of chalcopyrite decreased slightly with increasing pH but remained at a high level. Within the experimental range, the lowest recovery rate of chalcopyrite without SS was 88.65% (pH 11.79), while the lowest recovery rate after adding 150 mg / L SS was still 83.29% (pH 11.62). pH significantly affected the recovery rate of pyrite. The recovery rate of pyrite remained high under weakly alkaline conditions without SS, but under strongly alkaline conditions (pH 11.67), the recovery rate was only 23.63%, indicating that lime had a good inhibitory effect on pyrite under strongly alkaline conditions. After adding 150 mg / L SS, SS and lime exhibited a significant synergistic inhibitory effect under weakly alkaline conditions. At pH 9.34, the recovery rate of pyrite could be as low as 9.17%, while the recovery rate of chalcopyrite remained above 83%.

[0030] III. Experimental Examples Example 1, Zeta potential analysis. Before measurement, the oxide film on the mineral surface was removed, and the sample was stirred using a magnetic stirrer after cleaning. The mineral sample was treated according to the test conditions, and the slurry was prepared to a concentration of 0.02%. The pH was adjusted to a specific value using hydrochloric acid / sodium hydroxide. During measurement, the supernatant was pipetted and transferred to the sample cell for measurement. Each measurement was repeated three times, and the average value was taken. The results are shown in [Figure number missing]. Figure 2 Within the experimental range, the surface Zeta potential of both chalcopyrite and pyrite decreased with increasing slurry pH, while the surface charge increased. The isoelectric points of chalcopyrite, chalcopyrite + lime, chalcopyrite + SS, and chalcopyrite + lime + SS were located near pH 2.70, 2.91, 2.65, and 2.93, respectively; while those of pyrite, pyrite + lime, pyrite + SS, and pyrite + lime + SS were located near pH 3.17, 4.36, 2.48, and 3.35, respectively. On the chalcopyrite surface, only the cations dissociated from lime dominated the positive shift in Zeta potential, with SS having a weak effect. On the pyrite surface, the positive shift in isoelectric point was more significant when lime was added alone than that of chalcopyrite, while the negative shift occurred when SS was added alone. When both lime and SS were added simultaneously, the isoelectric point still showed a positive shift, but the magnitude of the positive shift was significantly smaller than that of lime alone, indicating that Ca... 2+ The simultaneous and synergistic adsorption of cations and SS enhances the surface's negative charge and hydrophilicity, thereby strengthening the inhibition effect.

[0031] Example 2, FT-IR analysis. A 10 μm sample was taken, the surface oxide film was removed, and the sample was stirred with a magnetic stirrer. After processing the sample according to the test conditions, the lower solid mineral layer was filtered and collected. The sample was rinsed three times with deionized water, vacuum dried, and its infrared spectrum was measured using the KBr pellet method. The results are shown in [Figure number missing]. Figure 3 SS exhibits typical polysaccharide characteristics, 3381.01 cm⁻¹ -1The broad, strong peak at 2931.08 cm⁻¹ belongs to the OH stretching vibration. -1 and 1369.58 cm -1 Corresponding to the stretching and bending vibrations of methylene CH, respectively, 1651.08 cm⁻¹ -1 The OH bending vibration of adsorbed / structured water, 994.04 cm. -1 Attributable to intramolecular hydrogen bond vibration of the hydroxyl group, 575.60 cm⁻¹ -1 Vibration of the sugar ring skeleton, 1158.91 cm. -1 (COC) and 1082.64 cm -1 (COH) is a strong characteristic absorption peak of SS.

[0032] Figure 3 In (a), chalcopyrite is found at 3441.24, 1629.67, 1430.94, 1022.21, 878.48 and 718.69 cm. -1 Vibrational peaks for adsorbed water, trace amounts of carbonates, and sulfates are observed. In the infrared spectrum of chalcopyrite + lime, each absorption peak shows only a slight blue shift (1–6 cm⁻¹). -1 No new peaks were generated. The OH peak in the infrared spectrum of chalcopyrite + SS appeared at 3435.67 cm⁻¹. -1 A significant blue shift (approximately 55 cm) compared to SS. -1 Compared to chalcopyrite, it exhibits a redshift (approximately 5.6 cm). -1 The spectrum shows only at 1434.87, 1243.93, and 1010.02 cm⁻¹. -1 Extremely weak CH and CO peaks were observed, while the strong characteristic absorption peak of SS was not seen, indicating that SS undergoes hydrogen bonding adsorption on the chalcopyrite surface, but exists only in a sparse state. The characteristic absorption peak of COC was still not observed in the infrared spectrum of chalcopyrite + lime + SS, only appearing at 1082.44 cm⁻¹. -1 The presence of a very weak COH peak indicates that neither of them was adsorbed in large quantities on the chalcopyrite surface.

[0033] Figure 3 In (b), pyrite is found at 3437.81, 1630.66, 1084.58, and 571.04 cm. -1 The infrared spectrum of pyrite + lime exhibits peaks for adsorbed water, trace amounts of sulfate, and Fe-S lattice vibrations. A new peak appears at 1362.62 cm⁻¹. -1 1020.05 cm -1 788.49 and 669.67 cm -1 Absorption peak, Fe-S peak from 571.04 cm⁻¹ -1 The redshift reached 541.97 cm. -1This indicates that lime induces lattice distortion in pyrite, leading to the formation of calcium carbonate and calcium sulfate precipitates, which then form a passivation film. In the infrared spectrum of pyrite + SS, the adsorbed water peaks in the high wavenumber region essentially disappear, while peaks at 1434.78, 1019.69, 787.42, and 669.43 cm⁻¹ appear in the mid-to-low wavenumber region. -1 A series of new peaks were observed, with Fe-S lattice vibrations increasing from 571.04 cm⁻¹. -1 The redshift reached 533.94 cm. -1 The redshift amplitude is approximately 37 cm. -1 This indicates that SS (sulfuric acid) interacts with iron ions on the pyrite surface via chemisorption or coordination with hydroxyl groups, forming an organic-inorganic hybrid interface layer. In the infrared spectrum of pyrite + lime + SS, the OH peak shifts blue to 3449.89 cm⁻¹. -1 1436.29 cm -1 and 876.36 cm -1 The presence of a pair of sharp CaCO3 characteristic peaks indicates that SS promoted the crystallization of calcium carbonate, resulting in highly crystalline calcite-type calcium carbonate; the sulfate peak appears at 1084.58 cm⁻¹. -1 The blue shifted to 1098.05 cm. -1 An increase of 673.44 cm -1 Peak, Fe-S peak (571.04 cm⁻¹) -1 The disappearance of the lattice vibrations indicates that the pyrite surface is covered by a dense calcified-organic composite film, which shields the lattice vibrations.

[0034] like Figure 4 As shown in Table 2, SO4 fumes newly appeared on the surface of the chalcopyrite + lime sample. 2- and Ca 2+ The results indicate that trace amounts of CaSO4 precipitate are present on the chalcopyrite surface, with the Cu(I)-S content increasing from 75.70% to 77.20% and the Fe(III)-SO4 content decreasing from 17.18% to 12.41%. The species composition of the chalcopyrite + SS sample remained unchanged, with the binding energy essentially constant; only the proportion of some species showed slight changes, indicating that SS did not directly participate in surface chemical modification. The CaSO4 content on the chalcopyrite + lime + SS sample surface... 2+ The increase from 1.56% to 2.62% indicates that SS promoted a small amount of CaSO4 precipitation on the chalcopyrite surface, while the other components showed little change and did not form an effective capping layer.

[0035] Table 2. Effects of lime and SS on the surface morphology of chalcopyrite.

[0036] like Figure 5 As shown in Table 3, the surface S2 of the pyrite + lime sample 2-The proportion decreased from 67.20% to 62.03%, S 2- The proportion decreased from 18.57% to 15.40%, S 2- The proportion increased from 7.80% to 15.12%, S2O3 2- The proportion increased from 2.38% to 3.39%, the proportion of Fe(III)-O / OH increased from 12.69% to 17.58%, and Ca was detected on the surface. 2+ Signal. S2 on the surface of pyrite + SS sample. 2- The proportion decreased from 67.20% to 63.23%, S 2- The proportion decreased from 18.57% to 16.43%, S 2- The proportion increased from 7.80% to 13.10%, S2O3 2- The proportion increased from 2.38% to 2.89%, and the proportion of Fe(III)-O / OH increased significantly from 12.69% to 18.56%, SO4 2- The proportion increased slightly from 4.05% to 4.37%. Compared with pyrite + lime or pyrite + SS, the surface Ca of the pyrite + lime + SS sample increased. 2+ The concentration increased to 1.50%, the Fe(III)-O / OH ratio increased to 20.66%, and S2 2- The proportion was 62.16%, S 2- The proportion was 15.23%, S 2- The proportion was 15.08%, S2O3 2- The proportion was 3.36%, SO4 2- The proportions were 4.17%, Fe(II)-S 47.23%, and Fe(III)-S 32.12%. The lime-induced low alkalinity environment enhanced the formation of Fe(III)-O / OH on the pyrite surface, providing more adsorption sites for SS and forming a thicker and denser hydrophilic film.

[0037] Table 3. Effects of lime and SS on the surface morphology of pyrite. Example 4: Flotation kinetics test and data fitting. Flotation kinetics tests were conducted using an XFG hanging flotation machine. Before measurement, the surface oxide film was removed, reagents were added, and the mixture was stirred, as in Example 1. After starting the aerated flotation, concentrate and tailings products were collected at eight sampling time points: 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 4 min, and 5 min. This was repeated five times. Samples from the same sampling time point were combined and used as the final product for filtration, drying, and weighing. The individual recovery rate at each sampling time point was calculated using formula (1), and the individual recovery rates at each sampling time point were accumulated sequentially to obtain the cumulative recovery rate sequence corresponding to the eight sampling time points, which served as the input data for flotation kinetics fitting.

[0038] The flotation behavior of chalcopyrite and pyrite under different reagent regimes was studied using the classical first-stage flotation kinetic model (Equation (2)). The cumulative recovery sequence obtained from the flotation experiment was fitted using MATLAB. The specific fitting process is as follows. First, the eight sampling time points were used to form a time vector t, and the corresponding eight cumulative recoveries were used to form a response vector ε. t The second step is to use the curve fitting tool in MATLAB to fit the curve to the custom equation ε shown in formula (2). t =ε ∞ (1 -e) -kt ) as the fitting model, with ε t Let k be the parameter to be estimated. The third step is to set the initial value for the iteration, ε. ∞ The initial value of is the measured cumulative recovery rate at a sampling time point of 5 min, and the initial value of k is 1 min. -1 ; Set parameter boundaries, ε ∞ The lower bound of is 0 and the upper bound is 100%, and the lower bound of k is 0 and the upper bound is 10 min. -1 The fourth step involves using a trust region algorithm for nonlinear least squares iteration, with the convergence objective being to minimize the sum of squares of the differences between the measured cumulative recovery rate and the model-calculated value. After convergence, the parameters to be estimated are output. The fitted values ​​of k and k.

[0039] Goodness of fit is determined by the coefficient of determination R. 2 Evaluation is calculated according to formula (3).

[0040] (Formula 3) In equation (3), ε t,i Let be the measured cumulative recovery rate at the i-th sampling time point. This is the model calculation value at the i-th sampling time point. R is the arithmetic mean of the cumulative measured recovery rates at the eight sampling time points. 2The closer the value is to 1, the better the model fits the experimental data.

[0041] Flotation kinetic data and fitting curves of chalcopyrite and pyrite under different reagent regimes are as follows: Figure 6 As shown in Table 4, the key parameters obtained from the fitting are as follows. Table 4 shows that the goodness of fit R1 of the classical first-stage flotation kinetic model to the experimental data is... 2 All values ​​exceeded 0.99, indicating a good fit. The ε values ​​for chalcopyrite under the experimental conditions... ∞ All values ​​were above 93%. Compared with direct flotation of chalcopyrite, the addition of lime and SS slightly decreased k, but still remained at a high level, indicating that lime and SS had a relatively small impact on the flotation of chalcopyrite. Unlike the flotation behavior of chalcopyrite, the addition of lime and SS resulted in a lower ε value for pyrite. ∞ The values ​​of ε and k vary considerably, especially for pyrite + lime or pyrite + SS. ∞ The percentages were 94.02% and 59.50%, respectively, and the k values ​​were 0.5750 min. -1 and 0.2883 min -1 Adding lime or SS alone can significantly reduce the flotation rate of pyrite, exhibiting a certain inhibitory effect; when lime and SS are added simultaneously, ε ∞ The percentage was 33.50%, and k was only 0.1524 min. -1 Under the synergistic effect of lime and SS, the flotation of pyrite is strongly inhibited.

[0042] Table 4. Fitting parameters for flotation kinetics of chalcopyrite and pyrite As a further processing of the fitted data, the dynamic selectivity coefficient η is defined. k The ratio of the flotation rate constant of chalcopyrite to that of pyrite under the same reagent regime is calculated according to formula (4).

[0043] (Formula 4) In equation (4), k 黄铜矿 and k 黄铁矿 These are the fitted values ​​of the flotation rate constants for chalcopyrite and pyrite under the same reagent regime. Substituting the data from Table 4 into equation (4), η is calculated for the synergistic system (lime and SS added simultaneously). k =0.9197 / 0.1524≈6.03, meaning the flotation rate of chalcopyrite is approximately 6.03 times that of pyrite. Combined with a short flotation window of 2 minutes, good copper-sulfur separation can be achieved kinetically. Correspondingly, the maximum theoretical recovery rate ε of chalcopyrite and pyrite in the synergistic system is... ∞The recoveries were 93.99% and 33.50%, respectively, with a difference of 60.49 percentage points. The above kinetic parameters were obtained solely by fitting the cumulative recovery sequence of Equation (1) to Equation (2) using nonlinear least squares, without relying on any additional algorithm model.

[0044] Based on Examples 1-2 and Experiments 1-4, it is evident that the adsorption layer structures formed by lime and SS on the surfaces of chalcopyrite and pyrite, and their effects on bond energies, exhibit significant differences. For chalcopyrite, lime only induces a slight blue shift in the absorption peak, and SS can only form a sparse adsorption layer; the synergistic effect of both is insufficient to achieve effective coverage, and the floatability of chalcopyrite remains almost unaffected. On the surface of pyrite, lime induces the formation of calcium carbonate and calcium sulfate precipitates, while SS reacts with Fe through hydroxyl groups. 3+ Coordination can cause a red shift in the Fe-S bond; under synergistic effect, the Fe-S lattice vibration is shielded, the crystallinity of calcium carbonate is increased, the hydroxyl peak is blue shifted, and a dense and ordered calcified-organic composite adsorption layer is formed, fundamentally changing the bond energy environment, thereby significantly enhancing the inhibition effect on pyrite.

[0045] The above description is only a preferred embodiment and test example of the present invention, and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for selectively suppressing pyrite in low-alkalinity copper-sulfur flotation separation, characterized in that, Saturated lime water is first added to a slurry containing chalcopyrite and pyrite to adjust the pH of the slurry to 9.0-10.0 and then stirred. Unmodified soluble starch is then added and stirred, followed by the addition of a collector and stirring. Subsequently, aeration flotation is performed, with chalcopyrite floating to the surface with the froth product and pyrite remaining in the product in the tank. During the flotation process, the soluble starch and the calcium species provided by the saturated lime water selectively form a calcification-organic composite hydrophilic film on the surface of pyrite. The calcification-organic composite hydrophilic film contains calcite-type crystalline calcium carbonate and soluble starch adsorbed on the surface of pyrite.

2. The method according to claim 1, characterized in that, The pH of the slurry is 9.2 to 9.

6.

3. The method according to claim 1, characterized in that, The soluble starch is soluble starch prepared from corn starch, and the mass concentration of the soluble starch in the slurry is 100-200 mg / L.

4. The method according to claim 3, characterized in that, The soluble starch in the slurry has a mass concentration of 150 mg / L.

5. The method according to claim 1, characterized in that, The collector is butyl xanthate, and the concentration of butyl xanthate in the pulp is 1×10⁻⁶. -4 mol / L.

6. The method according to claim 1, characterized in that, After adding saturated lime water, stir for 3 minutes; after adding soluble starch, stir for 3 minutes; after adding collector, stir for 2 minutes; the aeration flotation time is 2 minutes.

7. The method according to claim 1, characterized in that, The solids in the slurry are chalcopyrite and pyrite minerals with a particle size of -74 to +38 μm. The minerals are ultrasonically cleaned for 30 minutes before flotation to remove the surface oxide film.

8. The method according to claim 1, characterized in that, After the aerated flotation, the foam product and the product in the tank are collected separately, filtered, dried, and weighed, and the recovery rate ε is calculated according to formula (1). (Official 1) In the formula, w 精 For the quality of foam products, w 尾 The quality of the products in the tank.

9. The method according to claim 8, characterized in that, Foam products were collected at 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 4 min, and 5 min after the start of aerated flotation, and the cumulative recovery rate was calculated according to formula (1). The cumulative recovery rate was fitted using the classical first-stage flotation kinetic model according to formula (2). ε t =ε ∞ (1 -e -kt ) (Official 2) In the formula, ε t Let ε be the cumulative recovery rate at time t. ∞ The maximum theoretical recovery rate is given by k, where k is the flotation rate constant; the ε of the fitted pyrite is... ∞ The value is 30%–35%, and k is 0.14–0.17 min. -1 ε of chalcopyrite ∞ Less than 93%, k is not less than 0.90 min -1 Goodness of fit R 2 Greater than 0.

99.

10. The method according to claim 1, characterized in that, The infrared spectrum of the calcified-organic composite hydrophilic membrane is in the range of 1430–1440 cm⁻¹. -1 and 870–880 cm -1 The characteristic absorption peak of calcite-type calcium carbonate appears at 571 cm⁻¹. -1 The nearby Fe-S lattice vibration peaks disappear; after treatment by the method, the proportion of Fe(III)-O / OH component on the pyrite surface is not less than 18%, the flotation recovery rate of pyrite is not higher than 10%, and the flotation recovery rate of chalcopyrite is not less than 83%.

Citation Information

Patent Citations

  • A flotation method for high-sulfur gold-copper ore

    CN103691569B

  • Preparation method and application of inhibitor for copper-sulfur separation under weak acidic condition

    CN114011581A

  • Low-alkalinity inhibitor and method for pyrite in copper-sulfur ore containing secondary copper

    CN116532244A

  • Flotation method for arsenic-containing copper sulfide ore

    CN119838742A